Specificity factors in cytoplasmic polyadenylation - Charlesworth, Amanda; Meijer, Hedda A.; de Moor, Cornelia H. (Wiley, 2013)
Poly(A) tail elongation after export of an messenger RNA (mRNA) to the cytoplasm is called cytoplasmic polyadenylation. It was first discovered in oocytes and embryos, where it has roles in meiosis and development. In recent years, however, has been implicated in many other processes, including synaptic plasticity and mitosis. This review aims to introduce cytoplasmic polyadenylation with an emphasis on the factors and elements mediating this process for different mRNAs and in different animal species. We will discuss the RNA sequence elements mediating cytoplasmic polyadenylation in the 3′ untranslated regions of mRNAs, including the CPE, MBE, TCS, eCPE, and C-CPE. In addition to describing the role of general polyadenylation factors, we discuss the specific RNA binding protein families associated with cytoplasmic polyadenylation elements, including CPEB (CPEB1, CPEB2, CPEB3, and CPEB4), Pumilio (PUM2), Musashi (MSI1, MSI2), zygote arrest (ZAR2), ELAV like proteins (ELAVL1, HuR), poly(C) binding proteins (PCBP2, αCP2, hnRNP-E2), and Bicaudal C (BICC1). Some emerging themes in cytoplasmic polyadenylation will be highlighted. To facilitate understanding for those working in different organisms and fields, particularly those who are analyzing high throughput data, HUGO gene nomenclature for the human orthologs is used throughout. Where human orthologs have not been clearly identified, reference is made to protein families identified in man.